SOSIALISASI SEX EDUCATION DI PAUD SE-GUGUS ANYELIR KOTA BENGKULU - Zahratul Qalbi; Delrefi Delrefi; Latifah Gunarsih; Lifina Riskita K; Selpina Selpina; Wisman Wisman; Rafhi Febryan Putera (Universitas Mataram, 2022)
Cases of sexual violence against children are increasing so that it is enough to attract public attention. Immoral acts come even from those closest to the child who do not understand sexual education. Children are likely to find it difficult to fight the deviant treatment that occurs because of the lack of sex education for teachers and parents. Counseling about sex education is expected to be able to overcome these problems. This service is carried out to the community with the aim of increasing and increasing the understanding of teachers and parents regarding the importance of sex education in early childhood. Besides providing information and knowing how to teach sex education in the right way. The service activity was carried out at Bengkulu University online on Thursday, November 4, 2021, involving teachers and parents of early childhood children in Kindergartens throughout the Carnation Cluster, Bengkulu City, Bengkulu Province, with a total of 120 people. Workshop activities are carried out with lectures, discussions and questions and answers according to the literature review to provide and increase understanding about sex education. The results of community service activities, namely based on the results of the evaluation of sex education socialization activities as an effort to prevent abuse against children for teachers and parents in the Carnation Cluster of Bengkulu City, it can be concluded that the activity went successfully according to plan. This can be seen from the high percentage of participants related to the usefulness of the activity and the convenience for participants in understanding the material and more than 70% of participants want this service activity to be carried out again. The conclusion from community service is that partners have an understanding of the importance of sex education from an early age and know how to teach sex education to children appropriately.